1995
DOI: 10.1093/rheumatology/34.8.742
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Systemic Lupus Erythematosus and Long-Term Steroid Therapy on Bone Mass in Pre-Menopausal Women

Abstract: The aim of our study was to assess bone mineral density (BMD) in pre-menopausal women with systemic lupus erythematosus (SLE) and the influence of disease activity and use of corticosteroids. Lumbar and femoral BMD were measured in 43 patients with SLE (28 on regular steroid therapy, 15 with recent onset, non-treated) and compared with 43 healthy women matched for age. In addition, 21 SLE patients treated with corticosteroids were followed-up with a mean of 36.6 +/- 12.7 months. BMD was significantly lower in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
39
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 0 publications
9
39
1
Order By: Relevance
“…Steroids are a mainstay drug therapy in JDM and are a well-recognized cause of osteoporosis in other rheumatic diseases (17)(18)(19)(20)(21)(22)(23). Differently from other reports, our study showed that in children with JDM there is no significant correlation between bone mass and steroid use, a fact possibly due to the small number of patients included in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Steroids are a mainstay drug therapy in JDM and are a well-recognized cause of osteoporosis in other rheumatic diseases (17)(18)(19)(20)(21)(22)(23). Differently from other reports, our study showed that in children with JDM there is no significant correlation between bone mass and steroid use, a fact possibly due to the small number of patients included in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…After adjustment for cumulative dose and other variables, daily dose was not associated with BMD at any of those sites. Similar to the reports on cumulative dose, daily CS dose was found to be a predictor of BMD in some [15,35,[103][104] but not in other studies [14,[22][23][24]29,37,43,46,59,65,66,101].…”
Section: Relationship To Cs Dosesupporting
confidence: 82%
“…The cumulative dose of corticosteroids was found to be an important variable in explaining decreased bone mass in the femoral neck and lumbar spine. These findings are consistent with those of several studies in adult-onset SLE (6,(8)(9)(10) and contradict the results of other studies (4,38). Trapani et al also reported an association between the cumulative steroid dose and BMD in patients with childhood-onset SLE (13), whereas Castro et al did not observe such an association (12).…”
Section: Osteopenia In Patients With Childhood-onset Slesupporting
confidence: 81%
“…through decreased formation and increased resorption of bone (21,22), but the impact of corticosteroids on bone loss in the setting of SLE is unclear (6,9,10,19).…”
mentioning
confidence: 99%